Desarrollo de sistema informático para el control y seguimiento de mujeres en estado de gestación atendidas en el sistema básico de salud integral del departamento de Morazán - Benavides Romero, Laura María; Méndez Rodríguez, Wilber David; Romero Hernández, Carlos Edenilson; Sánchez Henriquez, Ana Ruth; Hernández Bonilla, Ligia Astrid (San Miguel : FMO, UES, 2020)
RESUMEN : Se considera al SIBASI, como la estructura básica porque reúne en el contexto local los elementos que plantea el Sistema Nacional de Salud, bajo la rectoría del Ministerio de Salud. Se considera operativa, porque desarrolla un Modelo de Atención Integral en Salud, por medio de una red de proveedores articulados armoniosamente; complementando los esfuerzos y evitando la duplicación de acciones entre éstos, haciendo un uso eficaz y eficiente de los recursos, facilitando el seguimiento de las actividades y evaluando los logros en términos del impacto sobre la salud de la población bajo su responsabilidad. Por ende el SIBASI cede Morazán, se ve afectado por esta problemática, ya que con el sistema que cuentan maneja la información de forma general; niños, adolescentes, adultos, mujeres en edad fértil, y adultos mayores; todos ellos se encuentran registrados en un mismo sistema, por lo cual se diseña un sistema de control y seguimiento para la solución de esta problemática.
ABSTRACT ABSTRACT: Currently there is a challenge for teachers Zone 2, Sector 13; Area 5, city of Chinameca, San Miguel with new advances in computing, however teachers have little or no training in computing. Human beings have to learn throughout their lives in order to take advantage of new learning and life possibilities, to be able to integrate into changing social systems and to be able to contribute to the progress and development of society.ABSTRACT: Currently there is a challenge for teachers Zone 2, Sector 13; Area 5, city of Chinameca, San Miguel with new advances in computing, however teachers have little or no training in computing. Human beings have to learn throughout their lives in order to take advantage of new learning and life possibilities, to be able to integrate into changing social systems and to be able to contribute to the progress and development of society.: SIBASI is considered as the basic structure because it brings together in the local context the elements proposed by the National Health System, under the leadership of the Ministry of Health. It is considered operational, because it develops a Comprehensive Health Care Model, through a network of harmoniously articulated providers; complementing efforts and avoiding duplication of actions among resources, making effective and efficient use of resources, facilitating the monitoring of activities and evaluating achievements in terms of the impact on the health of the population under their responsibility. Therefore, SIBASI, Morazán, it is affected by this problem, since with the system that it has, it manages the information in a general way; children, adolescents, adults, women of childbearing age, and older adults; all of them are registered in the same system, for which a control and monitoring system is designed to solve this problem.
Incluye referencias bibliográficas (hojas 338-341).